(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article examines the mechanisms for testing and supporting cotton-textile clusters on the part of government and non-government organizations, as well as forms of promoting the development of production cooperation within the economic cluster of business entities specializing in cotton-textile production.